Consumer Buying Behaviour in the Philippines Music Industry - Li, Jia (International Business Education Journal, 2021)
Increasing competition in the Philippines pop music industry demanded an investigation into consumer buying behaviour. Therefore, the study aims to describe the consumer buying behaviour of the Philippines music industry. Accordingly, 284 music buyers were sampled using the convenience sampling technique at two music stores in SM Baguio City, Philippines, and surveyed. Data were analyzed by using descriptive analysis. The findings indicate that most respondents purchased one music product in a single purchase (65.5%), preferred pop genre (20.1%), preferred music band (46.6%), preferred Sony (54.6%), spent 30 minutes on a music purchase (41.5%), buy music products one a month (56.3%), and spent PhP 200 or less for music monthly (55.3%). Hence, it is important for music stores managers who wish to expand the music industry to take consumer buying behaviour into foremost consideration. However, the actual behaviour of human being is such a complicated and overlapping manner that not all factors are at the same level of importance towards making choices, which calls for further exploration.